Development of polyvinylidene fluoride (PVDF) hollow fiber membranes by novel thermally induced phase separation - Zhao, Jie (2019)
Polyvinylidene fluoride (PVDF) has received growing attention in hollow fiber membrane preparation for water production and wastewater treatment due to its excellent physical and chemical properties. Currently, PVDF hollow fiber membranes prepared via the conventional non-solvent phase separation (NIPS) method are often subjected to the formation of macrovoids, resulting in a broad pore size distribution and weak mechanical strength. Another method—thermally induced phase separation (TIPS) has gained renewed interest as it can produce robust membrane with a narrow pore size distribution. However, limited studies on TIPS were focused on the control over the surface pore structure, which is the key to the selectivity and permeability of membranes. Therefore, the development of a novel method to fabricate membranes with tailorable surface pore size and strengthened structure is critical for the membranes applied in the water industry. This research aims to develop PVDF-based hollow fiber membranes via novel thermally induced phase separation. Firstly, the basic understanding of TIPS process was acquired by fabricating the hollow fiber membranes prepared using mild diluents. Subsequently, hydrophobically enhanced hollow fiber membranes with polytetrafluoroethylene (PTFE) addition were developed via TIPS method for direct contact membrane distillation (DCMD). Further, a novel hybrid method involving NIPS and TIPS (N-TIPS) was explored by using mixed diluents. Finally, the N-TIPS method was used to develop hydrophilically enhanced hollow fiber membranes with improved antifouling property by immobilizing Pluronic F127 particles.